Autonomic and baroreflex regulations in syndromic and non-syndromic aortopathies: a case–control study - Cairo, Beatrice; Udugampolage, Nathasha Samali; Gelpi, Francesca; Bari, Vlasta; Salvi, Paolo; Angolani, Miriam; Taurino, Jacopo; Porta, Alberto; Pini, Alessandro (Frontiers in Physiology, 2026)
Baroreflex regulation is directly influenced by the mechano-sensitive properties of the baroreceptors. The mechanical and dimensional properties of the aorta are affected in patients with thoracic aortic aneurysm (TAA). We hypothesize that the baroreflex sensitivity (BRS) is modified in TAA patients and that these modifications might be different when the TAA group is divided into syndromic (Synd) and non-syndromic (NonSynd) patients. The aim of the study is to evaluate autonomic and baroreflex control in patients with Synd and NonSynd TAAs. We enrolled 80 TAA patients and divided them into Synd (N = 46) and NonSynd (N = 34) groups. The two groups did not differ in either demographic factors or pharmacological therapy. Autonomic function and BRS, assessed from the heart period (HP) and systolic arterial pressure (SAP) variability, were compared to those of age- and gender-matched healthy controls (HCs, N = 28). Analyses were carried out in the low-frequency (LF, 0.04 Hz–0.15 Hz) and high-frequency (HF, 0.15 Hz–0.4 Hz) bands. The Synd and NonSynd subgroups did not show any significant differences in terms of autonomic control or BRS. We observed that, in the LF band, BRS was lower in TAA patients than in HCs during rest in the supine position (REST), while it was similar during active standing (STAND). STAND reduced the power of HP variability in the HF band and BRS in the LF band while increasing the power of SAP in the LF band in both HCs and TAA patients. Since BRS was lower at REST in both Synd and NonSynd TAA groups than in the HC group, we conclude that BRS is affected by either the dimensional or the mechanical properties of the aorta in relation to the pathology.